Isotopic offsets between bulk plant water and its sources are larger in cool and wet environments - de la Casa, Javier; Barbeta, Adrià; Rodríguez-Uña, Asun; Wingate, Lisa; Ogée, Jérôme; Gimeno, Teresa E. (Hydrology and Earth System Sciences, 2022)
Isotope-based approaches to study plant water sources rely on the assumption that root water uptake and within-plant water transport are non-fractionating processes. However, a growing number of studies have reported offsets between plant and source water stable isotope composition for a wide range of ecosystems. These isotopic offsets can result in the erroneous attribution of source water used by plants and potential overestimations of groundwater uptake by the vegetation. We conducted a global meta-analysis to quantify the magnitude of these plant source water isotopic offsets and explored whether their variability could be explained by either biotic or abiotic factors. Our database compiled 112 studies spanning arctic to tropical biomes that reported the dual water isotope composition (δ2H and δ18O) of plant (stem) and source water, including soil water (sampled following various methodologies and along a variable range of depths). We calculated plant source 2H offsets in two ways: a line conditioned excess (LC-excess) that describes the 2H deviation from the local meteoric water line and a soil water line conditioned excess (SW-excess) that describes the deviation from the soil water line, for each sampling campaign within each study. We tested for the effects of climate (air temperature and soil water content), soil class, and plant traits (growth form, leaf habit, wood density, and parenchyma fraction and mycorrhizal habit) on LC-excess and SW-excess. Globally, stem water was more depleted in 2H than in soil water (SW-excess < 0) by 3.02±0.65 ‰ (P < 0.05 according to estimates of our linear mixed model and weighted by sample size within studies). In 95 % of the cases where SW-excess was negative, LC-excess was negative, indicating that the uptake of water that had not undergone evaporative enrichment (such as groundwater) was unlikely to explain the observed soil–plant water isotopic offsets. Soil class and plant traits did not have any significant effect on SW-excess. SW-excess was more negative in ...